Development of G-Sites-Based Character Education Media Assisted by Augmented Reality with the PBL Model in Elementary Schools - Tri Yanti Sari; Makmum Raharjo; Syarifuddin (Postgraduate, University of Mataram, 2025)
This study aims to produce a valid, practical, and effective G-sites-based character education learning media assisted by Augmented Reality with the PBL model in Elementary Schools for student learning outcomes. This study was conducted in grade V of SDN 3 Sukamaju, with 46 students as research subjects. The type of research used is Research Development (RD) with the ADDIE development model and Tessmer Evaluation. Data were collected through interviews, observations, expert reviews, one to one, small groups, and pretest-posttest. The results showed that the average validity by media experts was 85%, validity by material experts was 86%, and validity by language experts was 91% with a very valid category, the practicality score at the one to one stage was 80.66% with a very practical category, and the small group results obtained were 85% including the very practical category. Furthermore, the effectiveness of G-sites-based learning media assisted by Augmented Reality can be seen from the learning outcomes of students measured through field trials in pretest activities of 50.69% and posttest with an average value of 84.56% and N-Gain of 0.77 which is included in the high category. It can be concluded that G-Sites-based learning media assisted by Augmented Reality is proven to be valid, practical, effective and very suitable for use in instilling character education in grade V Elementary School students.